Functional outcome of tibial plateau fractures treated by ORIF using three-column classification (TCC) - Lakhey, Shishir; Jha, Daman Kumar; Thapa, Abhishek; Rana, Raj; Chitrakar, Niva; Thakur, Jitendra; Poudel, Amit (Nepal Orthopaedic Association Journal, 2025)
BACKGROUND Treatment of tibial plateau fractures remains challenging especially those caused by high energy trauma. Despite operative treatment, these fractures often result in complications like malalignment and secondary osteoarthritis (OA). A clearer understanding of the fracture pattern may help decrease these complications. As fracture configuration are better evaluated by CT scan, three column classification (TCC) seems to be useful in guiding the surgical management and planning surgical fixation of these fracture. The aim of this study is to evaluate the functional outcome of tibial plateau fractures treated by ORIF using TCC. METHODS All patients with proximal tibia fracture who were treated with open reduction and internal fixation (ORIF) between January 2019 - December 2022 were retrospectively identified and analysed using the hospital data base. A total of 30 patients were enrolled in this study. Preoperative radiographs, Preoperative CT scan, immediate post-operative and two year post-operative radiographs were analysed. Functional outcome was evaluated by Oxford knee score (OKS) and residual pain using Visual Analog Score (VAS). RESULTS All fractures were united in 4 months post op. The Functional outcomes measured by OKS was a mean of 43 (range: 23-48), which indicated good to excellent outcomes and patients had minimal residual pain of VAS score 1 (range: 0 to 5). CONCLUSION TCC seems to be a useful classification to plan the operative management of tibial plateau fractures.